Queer Postcolonial Narratives and the Ethics of Witnessing - McCormack, Donna (New York : Bloomsbury Academic, 2014)
'Queer Postcolonial Narratives and the Ethics of Witnessing is a critically engaged exploration of power and its relation to ethics and bodies. By revisiting and revising Judith Butler's and Homi Bhabha's queer and postcolonial theories of literary performance, McCormack expands current understandings of the performative workings of power through an embodied, multisensory ethics. That remembering is an embodied act which necessitates an undoing of one's sense of self captures how colonial and familial histories silenced by hegemonic structures may only emerge through opaque bodily sensations. These non-institutionalised forms of witnessing serve both to reconfigure theories of performativity, by re-situating the act of witnessing as integral to the workings of power, and to interrogate the current emphasis on speech in trauma studies, by analysing the multifarious, communal and public ways in which memories emerge. In Queer Postcolonial Narratives and the Ethics of Witnessing the body is reinstated as central to both the workings of and the challenges to colonial discourses'--
Includes bibliographical references : (pages 195-219) and index.
Includes bibliographical references and index.
Keywords: Power (Social sciences) in literature; Witnesses in literature; Postcolonialism in literature; Violence in literature; Queer theory; Testimony (Theory of knowledge).